Boletim Oficial de Macau (1998)
Keywords: 1.Conservation 保護; Good

Boletim Oficial De Macau (1998)
Keywords: 1.Conservation 保護; Good

Boletim Oficial de Macau (1998)
Keywords: 1.Conservation 保護; Good

Boletim Oficial de Macau (1998)
Keywords: 1.Conservation 保護; Good

Boletim Oficial de Macau (1998)
Keywords: 1.Conservation 保護; Good

Boletim Oficial de Macau (1998)
Keywords: 1.Conservation 保護; Good

Boletim Oficial de Macau (1998)
Keywords: 1.Conservation 保護; Good

Boletim Oficial de Macau (1998)
Keywords: 1.Conservation 保護; Good

Boletim Oficial de Macau (1998)
Keywords: 1.Conservation 保護; Good

Boletim Oficial de Macau, Suplemento (1998)
Keywords: 1.Conservation 保護; Good

Collins Spanish dictionary plus grammar (HarperCollins, 1998)
This two-in-one dictionary and grammar contains 80,000 references and 115,000 translations. It aims to help the user understand the language of the Spanish media and contemporary literature and includes business and computing terminology. It also has entries on aspects of Spanish life and culture.
OCLC: 37464605
Keywords: Dictionaries; DictionariesDictionariesChinese language Dictionaries English; DictionariesDictionariesChinese language Dictionaries French; DictionariesDictionariesDictionaries; DictionariesDictionariesDutch language Dictionaries English; DictionariesDictionariesEncyclopedias and dictionaries; DictionariesDictionariesEncyclopedias and dictionaries Specimens; DictionariesDictionariesEnglish language 20th century Dictionaries; DictionariesDictionariesEnglish language 20th century Dictionaries Chinese; DictionariesDictionariesEnglish language Australia Dictionaries; DictionariesDictionariesEnglish language Dictionaries; DictionariesDictionariesEnglish language Dictionaries Chinese; DictionariesDictionariesEnglish language Dictionaries Dutch; DictionariesDictionariesEnglish language Dictionaries French; DictionariesDictionariesEnglish language Dictionaries Latin; DictionariesDictionariesEnglish language Dictionaries Portuguese; DictionariesDictionariesEnglish language Dictionaries Spanish; DictionariesDictionariesEnglish language Idioms - Dictionaries; DictionariesDictionariesEnglish language Idioms Dictionaries; DictionariesDictionariesEnglish language New words Dictionaries; DictionariesDictionariesEnglish language Orthography and spelling Dictionaries; DictionariesDictionariesEnglish language Pronunciation Dictionaries; DictionariesDictionariesEnglish language–Dictionaries–Spanish; DictionariesDictionariesFrench language Dictionaries Chinese; DictionariesDictionariesFrench language Dictionaries English; DictionariesDictionariesFrench language French-English; English-French dictionaries; DictionariesDictionariesItalian language Dictionaries; DictionariesDictionariesLatin language Dictionaries English; DictionariesDictionariesLatin language Dictionaries French; DictionariesDictionariesMultilingual dictionaries; DictionariesDictionariesPortuguese language - Portuguese & English dictionaries; DictionariesDictionariesPortuguese language Dictionaries Chinese; DictionariesDictionariesPortuguese language Dictionaries English; DictionariesDictionariesSpanish language Dictionaries English; DictionariesDictionariesSpanish language–Dictionaries–English; DictionariesDictionariesdictionaries; DictionariesDictionariespolyglot dictionaries; English language; Espagnol (Langue) Grammaire; Spanish language; Spanish language Grammar; Spanish language–Grammar

葡文讀音三十講= Pronùncia portuguesa em trinta lições (澳門教區社會傳播中心, 1998)
printed in macau
Keywords: Portugais (Langue) Prononciation Aides audiovisuelles; Portuguese language Pronunciation Audio-visual aids; 葡語 發音 視聽輔助

Canticum Novum - Choi, S. A. Peter (Catholic Truth Society, 1998)
2 copies
Keywords: Hymns; English

Canticum Novum I - Choi, S. A. Peter (Catholic Truth Society, 1998)
OCLC: 912730024
Keywords: Hymns; English

Merriam-Webster's pocket guide to English usage - Gilman, E. Ward (Goyal Publishers & Distributors, 1998)
OCLC: 1136301371
Keywords: Dictionaries; English language Usage; English language Usage Dictionaries

Dialogos Modulo 5 Nivel intermedio - Parrinha, Maria Manuel; De Lurdes Costa, Maria; Santos, Sara (Instituto Portugues do Oriente, 1998)
2 copies, printed in macau
Keywords: Portuguese language; Portuguese language Textbooks for foreign speakers Chinese; Textbooks for Chinese speakers

漢語教程一至四冊生詞表 = Vovabulary of Mandarin Manual Level I - IV - Sheng, Yan; Ou, Qichao (Instituto Politécnico de Macau, 1998)
printed in macau

漢語教程第二冊 = Mandarin Manual Level II - Sheng, Yan; Ou, Qichao (Instituto Politécnico de Macau, 1998)
printed in macau

漢語教程第五冊 (上) = Mandarin Manual Level V (A) - Sheng, Yan; Ou, Qichao (Instituto Politécnico de Macau, 1998)
2 copies; printed in macau

漢語教程第五冊 (下) = Mandarin Manual Level V (B) - Sheng, Yan; Ou, Qichao (Instituto Politécnico de Macau, 1998)
2 copies; printed in macau

Obras Completas, Padre Antonio Vieira, Sermoes - Vieira, António (Typographia Minerva Central, 1998)
OCLC: 221313826
Keywords: 18.Bookworm; Catholic Church; Catholic Church Sermons; Condition: Fair; Religion; Sermons; Sermons; Portuguese; Église catholique Sermons

Obras Completas, Padre Antonio Vieira, Sermoes - Vieira, António (Typographia Minerva Central, 1998)
OCLC: 221313826
Keywords: 10.Cover Damage; 2.Damage; Catholic Church; Catholic Church Sermons; Condition: Fair; Religion; Sermons; Sermons; Portuguese; Église catholique Sermons

Obras Completas, Padre Antonio Vieira, Sermoes - Vieira, António (Typographia Minerva Central, 1998)
OCLC: 221313826
Keywords: 10.Cover Damage; 2.Damage; Catholic Church; Catholic Church Sermons; Condition: Fair; Religion; Sermons; Sermons; Portuguese; Église catholique Sermons

Obras Completas, Padre Antonio Vieira, Sermoes - Vieira, António (Typographia Minerva Central, 1998)
OCLC: 221313826
Keywords: 10.Cover Damage; 2.Damage; Catholic Church; Catholic Church Sermons; Condition: Fair; Religion; Sermons; Sermons; Portuguese; Église catholique Sermons

Obras Completas, Padre Antonio Vieira, Sermoes - Vieira, António (Typographia Minerva Central, 1998)
OCLC: 221313826
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Catholic Church; Catholic Church Sermons; Condition: Fair; Hard Cover; Religion; Sermons; Sermons; Portuguese; Église catholique Sermons

Obras Completas, Padre Antonio Vieira, Sermoes - Vieira, António (Typographia Minerva Central, 1998)
OCLC: 221313826
Keywords: 10.Cover Damage; 2.Damage; Catholic Church; Catholic Church Sermons; Condition: Fair; Religion; Sermons; Sermons; Portuguese; Église catholique Sermons

Dialogos... 4º Modulo Caderno do Aluno - Viola da Silva, Carlos; Piedade, Emila; Fonseca, Ligia; Cachapa Coimbra, Conceição (Instituto Portugues do Oriente, 1998)
12 copies, printed in macau
Keywords: Portuguese language; Portuguese language Textbooks for foreign speakers Chinese; Textbooks for Chinese speakers

Dialogos... 5º Modulo Caderno do Aluno - Viola da Silva, Carlos; Piedade, Emila; Fonseca, Ligia; Cachapa Coimbra, Conceição (Instituto Portugues do Oriente, 1998)
printed in macau
Keywords: Portuguese language; Portuguese language Textbooks for foreign speakers Chinese; Textbooks for Chinese speakers

Dialogos Modulo 4 Nivel Elementar - Viola da Silva, Carlos; Piedade, Emila; Fonseca, Ligia; Cachapa Coimbra, Conceição (Instituto Portugues do Oriente, 1998)
13 copies, printed in macau
Keywords: Portuguese language; Portuguese language Textbooks for foreign speakers Chinese; Textbooks for Chinese speakers

禮樂集11 - 劉, 志明; 蔡, 詩亞; 蘇, 柏羲 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 1998)

禮樂集12 - 劉, 志明; 蔡, 詩亞; 蘇, 柏羲 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 1998)

漢語大字典 - 漢語大字典, 編輯委員會 (宏建出版社, 1998)

中文一分鍾. 叁 - 陳永明 (中華書局, 1998)
OCLC: 42025609
Keywords: Chinese language; Chinois (Langue)

中文一分鍾. 壹 - 陳永明 (中華書局, 1998)
OCLC: 42025609
Keywords: Chinese language; Chinois (Langue)

中文一分鍾. 貳 - 陳永明 (中華書局, 1998)
OCLC: 42025609
Keywords: Chinese language; Chinois (Langue)